Faktor-Faktor yang Berhubungan dengan Kejadian Respiratory Distres Syndrom pada Neonatus di Ruang Perinatologi RSUD Kolonel Abundjani Bangko Kabupaten Merangin - Astari Seto; Elma Melia Sari (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
Neonatal mortality rates in the world are still high, in Indonesia in 2020 the IMR was 9.30 per 1,000 live births. The cause of IMR is respiratory complications caused by respiratory distress. RDS is a term used for respiratory dysfunction in neonates. This syndrome is a disease associated with delayed development of lung maturity. RSUD Colonel Abundjani Bangko recorded neonate mortality rate as many as 10 cases of death caused by Respiratory Distress Syndrom (RDS) from 39 cases of RDS in the Perinatology Room for the period 2022 to 2023. The purpose of this study was to determine the factors associated with the incidence of Respiratory Distress Syndrome (RDS) in neonates at Colonel Abundjani Hospital. This study was a case control analytic study using a retrospective approach. This research was conducted at Colonel Abundjani Bangko Hospital in 2024. The population in this study were all neonate patients who were treated in the Perinatology room of Colonel Abundjani Bangko Hospital with a total sample of 39 people. The results of this study indicate that there is a relationship between gestational age, parity and type of delivery on the incidence of RDS where the p-value <0.05 which means Ha is accepted. Colonel Abundjani Hospital is expected to be able to provide education to pregnant women who visit Colonel Abundjani Bangko Hospital, so that pregnant women get better information about RDS.